Seasonal performance assessment of four riverbank filtration sites by combined non-target and effect-directed analysis. (December 2020) - Oberleitner, Daniela; Stütz, Lena; Schulz, Wolfgang; Bergmann, Axel; Achten, Christine
Abstract: Targeting the most relevant organic micropollutants (OMP) in routine analysis appears difficult due to formation of transformation products of unknown concentration or toxicity. Performance assessment of water purification processes is still based upon limited target data. Therefore, we broadened the assessment of the removal efficiencies with combined non-target and effect-directed analysis at four riverbank filtration (RBF) sites in Germany. To assess micropollutant elimination, constancy and formation during different seasons, considering local redox conditions, travel distances and total component number in the river, non-target analysis features were grouped into categories. Furthermore, RBF sites were investigated with four endpoints (baseline toxicity, acetylcholinesterase inhibition, antibiotic effects and estrogenic effects) for thin-layer chromatography - effect-directed analysis for the first time. Results showed elimination or reduction of many features and effects, but also constancy and formation of varying proportions. Fall river samples showed precipitation-caused dilution in both tests. Spring samples showed increased effects only in acetylcholinesterase inhibition and estrogenic effects, probably due to phytoestrogens or algae bloom during vegetation period. Sites were ranked considering the total number of features, group proportions, seasonal variations and intensity and number of effects in abstraction wells. Oxic conditions and low initial component numbers in the river (Ruhr sites) resulted in less effects and fewer formations. Longer travel distances were important for a more efficient reduction of effects and features. Combination of non-target and effect-directed analysis proved to be valuable for a more comprehensive assessment of process performance beyond target analysis as also unknown OMP are observed with both methods. Graphical abstract: Image 1 Highlights: Combined non-target and effect-directed analysis valuable for process assessment. Low component numbers in river lead to reduced effects in production wells. First application of effect-directed analysis on riverbank filtration.